(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article analyzes modern approaches to improving the system of training highly qualified specialists in the water management system of Uzbekistan and the integration of science, education and production as the most effective ways to address this urgent issue. Nowadays the training of highly qualified specialists with practical experience on effective use of water resources one of the key issues is in Uzbekistan. In this article, solutions for the development of science-education and production integration in water management enterprises are developed.